Road through midnight : a civil rights memorial - Ingram, Jessica (Documentary arts and culture., 2020)
"In this book, Jessica Ingram presents photographs of landscapes that, to unaware passersby, look like nearly any other place in the Deep South: a fenced-in backyard, a dirt road covered with overgrowth, a field grooved with muddy tire prints. However, these seemingly ordinary places hold pivotal, often tragic, stories of the civil rights movement, though rarely is there a plaque with dates or names or any manmade indication of their importance. Most of these "un-memorialized" places are where bodies of African Americans-activists, paper mill workers, sharecroppers, and children-were found, victims of racial violence. These images are interspersed with oral histories from victims' families, journalists, and investigators, as well as newspaper microfiche, FBI files, and other archival ephemera. The narrative intensity grows in power, complexity, and depth as the book goes on and the history unfolds"--